2023
DOI: 10.1002/ece3.9880
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation management shapes arthropod and bird communities in an African savanna

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Our finding of no significant relationship between insect richness and proxies for plant biomass was unexpected. Previous studies of moths in South African savannahs (Delabye et al, 2022a) and various groups of herbivorous and other arthropods in KNP (Parker et al, 2023) suggested that primary productivity and vegetation complexity, both associated with plant biomass, are key drivers of insect diversity. However, these studies did not include plant diversity in their analyses of potential drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of no significant relationship between insect richness and proxies for plant biomass was unexpected. Previous studies of moths in South African savannahs (Delabye et al, 2022a) and various groups of herbivorous and other arthropods in KNP (Parker et al, 2023) suggested that primary productivity and vegetation complexity, both associated with plant biomass, are key drivers of insect diversity. However, these studies did not include plant diversity in their analyses of potential drivers.…”
Section: Discussionmentioning
confidence: 99%
“…In savannah ecosystems, plant communities play a key role in determining insect distribution and diversity (e.g., Leal et al, 2016;Parker et al, 2023). According to the resource specialization hypothesis, high plant diversity provides resources for more herbivorous insect species (e.g., Du et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The drop-plate meter and data collected using it met all expectations, being cost effective, easy to construct and operate, quick to deploy, and proving to generate reliable and robust predictors of plant biomass. This approach’s effectiveness is evidenced by its continued use in other habitats around the world ( Vermeire et al, 2021 ; Parker et al, 2023 ). The model generated using data from all crop systems showed that drop-plate measurements significantly predicted plant biomass across a wide swath of agroecosystems and geographic regions that varied substantially in plant community characteristics.…”
Section: Discussionmentioning
confidence: 99%